The Extreme Searcher's Internet Handbook: A Guide for the Serious Searcher - Margaret Henderson (Issues in Science and Technology Librarianship)
The article reviews The Extreme Searcher's Internet Handbook: A Guide for the Serious Searcher. Randolph Hock. Medford, NJ: CyberAge Books, 2004. 356 p. (ISBN 0-910965-68-4)